DIAGNOSIS DAN PENATALAKSANAAN ARTRITIS SEPTIK - Dary, I Wayan; Raka Putra, Tjokorda (journal of internal medicine, 2009)
Septic arthritis which caused by bacterial infection is a serious disease and still as challenge to physician because theprognosis has not improved significantly over the past two decades. The route of spread infection to joint through hematogenousor other routes include direct inoculation through joint prosthetic. The most often aetiology is Staphylococcus aureus. The processof native joint infection can be divided into three steps: bacterial colonization, establishing an infection, and induction ofhost inflammatory response. The diagnosis of septic arthritis rests on isolation of the pathogen from joint fluid. If we find classicsign and symptoms associated septic arthritis should not to delay the diagnosis of septic arthritis. Once septic arthritis is suspectedand the proper sample for microbiologic studies are collected, appropriate antibiotic treatment and adequate joint drainage shouldbegin immediately. The aim management of septic arthritis mainly are joint decompression, joint sterilization, and reserve jointfunction. Sterilization joint with empirical antibiotic based on gram stain and co-morbid disease and than adjusted base onbaterial culture result. Antibiotic should be administrated intravenously at least 2 weeks than continued orally. Joint decompressioncan be achieved by a variety methods include closed-needle aspiration, tidal irrigation, arthroscopy, and arthrotomy. Prophylacticuse of antibiotics is controversial for events posing a risk of haematogenous bacterial arthritis through transientbacteraemia. Prognosis of septic arthritis is poor since a permanent reduction in joint function is seen in approximately 30% ofpatients.